1964
DOI: 10.1177/107769906404100301
|View full text |Cite
|
Sign up to set email alerts
|

Some Correlates of Media Credibility

Abstract: What kinds of people place their greatest trust in television, or radio, or the newspaper, as a news medium? This study shows differences due to age, sex, education, place of residence and socioeconomic status. and socioeconomic status, as well as political preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
14

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 0 publications
2
51
1
14
Order By: Relevance
“…The notion of incongruence between a preferred media channel and the channel actually used is not unusual. Bucy (2003) and Westley and Severin (1964a) both referenced similar findings in their respective studies. Bucy (2003) found that adults and college students rated media channels with which they were less familiar as more credible.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The notion of incongruence between a preferred media channel and the channel actually used is not unusual. Bucy (2003) and Westley and Severin (1964a) both referenced similar findings in their respective studies. Bucy (2003) found that adults and college students rated media channels with which they were less familiar as more credible.…”
Section: Resultssupporting
confidence: 73%
“…Bucy (2003) found that adults and college students rated media channels with which they were less familiar as more credible. Additionally, Westley and Severin (1964a) reported that "residents did not necessarily assign greatest credibility to the medium they assigned greatest preference" (p. 326).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Este planteamiento funcionalista conceptualiza la credibilidad como un concepto unidimensional. Es el más habitual en las 82 encuestas de opinión (Westley & Severin, 1964;Shaw, 1973;Roper, 1977Roper, , 1985Mulder, 1980;Berg & Keifer, 2006 (2004,2006), el medio que consiguió la mejor calificación en una escala de 1 a 10 en 2006 fue la prensa especializada (M=7.06). El que obtuvo la peor fue la televisión (M=5.13).…”
Section: El Enfoque Comparativounclassified
“…Los primeros modelos teóricos planteaban la incidencia de variables demográficas en la atribución de la credibilidad. Así, algunos trabajos han señalado que los hombres otorgan más credibilidad a las noticias de los periódicos que las mujeres (Westley & Severin, 1964;Abel & Wirth, 1977;Mulder, 1981;Gunther, 1992 De hecho, los grados de afectividad y los aspectos emocionales de los medios han sido finalmente incluidos en los modelos, siendo estas posibles asociaciones las que merecen un mayor desarrollo futuro en lo teórico. Los estudios han descubierto que la credibilidad atribuida está robustamente relacionada con que las personas dependan o prefieran un medio para informarse (Wanta & Hu, 1994 …”
Section: Asociación Con Otras Variablesunclassified